Reshaping university of the future: designing business models that are relevant through humanising education and 4IR - Winasis, Fukky; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
The varied societal pressure placed on the university have generated discussion about the need to redefine the role of universities to better serve the needs of contemporary society. Some argue that the universities are still the only institution in society. On the other hand, universities have some experience problems with fees and graduation which make the universities’ value have to be questioned. Universities have to learn how to survive and thrive by having a strategy canvas with business modeling tools such as Business Model Canvas, Value Proposition Design Canvas and Environmental Map that used to evaluate, analyze, formulate and design the business models for the University of the Future. In addition, Universities have to adapt to the digital transformation where the voice of the customer is more prevalent than ever. It turns a customer into advocates for the university that become the most powerful marketing tools. Humanizing education should be implemented within the university to keep in sustainability and stay relevant with the future objective of universities. This paper provides the business models, strategies and plans to transform the university from faceless organization into a vibrant institution with human values such as morality and integrity.